Evaluating and comparing the impact of "sanctions" and "mismanagement" on the implementation process of the National Petroleum Company's facilities - Mehdi Ahmadi; Sayyed Fathullah Sajedi (مهندسی و مدیریت ساخت, 2020)
The purpose of the present study was to evaluate and compare the impact of "sanctions" and "mismanagement" on the implementation process of the National Petroleum Zones Company's facilities. The present study was applied in terms of deductive-inductive method and in terms of purpose. The statistical population includes all managers, deputies and experts of the National Iranian Oil Company (NIOC), including 200 people. The sample size was 131 using Cochran formula. The research instrument was a researcher-made questionnaire. AHP technique was used in this study. Also by paired comparisons and AHP method using Expert Choice software. For this purpose, using the hierarchical approach, the hierarchical tree was first formed using this method, then the alternatives were evaluated according to the criteria and then the factors based on the objective function were investigated and then using The hierarchical approach was first to form a hierarchy tree, and then to examine the options examined to evaluate and compare the impact of sanctions and mismanagement on the implementation process of the National South Oil Company's facility design projects, and to manage managers' knowledge, human resources management, and trans-organizational factors, respectively. , Ethical Behavior of Managers, Science and Ph Innovation, finance and banking, economics, logistics and commodities had a major impact on the implementation process of the National South Oil Company's facilities. Further mismanagement of the sanctions also affects the process of implementation of the National Petroleum Company's facilities.